A Cross Continental Comparison between India and America: The Global Outsourcing Destination - Sivadas, Sruthi (2009)
The significance of outsourcing has become increasingly important in the recent years. Companies worldwide are adopting outsourcing as a business strategy to compete in the global market. Decisions concerning outsourcing are not simple to take as they require careful consideration of all the factors that would affect the organisation as a result of outsourcing. I have tried to determine the factors that affect the outsourcing decision in American companies. I have also focused on India and why companies from the United States are attracted to India as an outsourcing destination. The aspects that motivate American companies to outsource to India have been discussed. Outsourcing is extremely significant in India. The nation has developed considerably due to outsourcing. Employment rates have gone up, education has improved and there is overall economic growth. Throughout the research, I have tried to gain a deep insight on the factors affecting the outsourcing decision and the reasons why India has been chosen as an outsourcing destination.